A Tsunami-Related Life History of Survivors in Banda Aceh, Indonesia and Sendai, Japan - Agus Suwignyo (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
In tsunami risk-reduction programs the survivors’ life history provides first-hand information about how they responded during and after a catastrophe. However, knowledge of tsunami-related experiences is not always systematically managed and institutionally communicated across generations. Some risk reduction programs lack of informed knowledge of tsunami-related experiences and consequently tend to be insensitive towards survivors’ life history. The aim of this paper is to examine how tsunami survivors constructed their tsunami-related knowledge and collective memories, taking the cases of Banda Aceh, Indonesia after the 2004 tsunami and Sendai, Japan after the 2011 tsunami. This paper, in particular, seeks to explore how the survivors’ experience helped to institutionalize their tsunami-related knowledge in a transferrable risk-reduction consciousness. Using first-hand interviews as well as interview recordings which were accessible online, this paper argues that in both cases of tsunami survivor cohorts, knowledge of tsunami-related experience was constructed through survival strategies and recovery processes in the aftermath of the events. Knowledge of survival strategies was constructed over time; and the longer period from the time of event, the more tacit the knowledge was. The process of knowledge construction was systematic in the Sendai case but was vernacular in the Banda Aceh case. However, in both cases the need for more engaged institutional communication between the government agencies and the people was evident.